Etymographic treatment of calques in the etymological dictionary by Petar Skok - Vučković Marija D. (Južnoslovenski Filolog)
The place of calques (loan translations) in etymological dictionaries is still an under-researched topic, and from a methodological point of view, it should be systematically studied how calques have been treated in etymological lexicography so far and, based on the results of those studies, draw up guidelines for the lexicographic aspect of interpretation of their origin. In this paper, which is a contribution to the mentioned research, the method of treatment of calques in the Etymological Dictionary of the Croatian or Serbian Language (Etimologijski rječnik hrvatskoga ili srpskoga jezika) by Petar Skok is considered. In his dictionary, written in the mid-20th century, P. Skok paid great attention to the lexemes created by calqueing, and for the purposes of this research, extensive material was collected and analyzed. Since, at the time when the dictionary had been compiled, the domestic linguistic terminology in this area was in the initial phase of formation, the repertoire of terminological and non-terminological means with which Skok referred to the process and results of calqueing is examined. Although the bulk of calques are made up of lexemes, other types of calqued linguistic units are also identified, the origin of which was the subject of discussion in Skok’s dictionary. Next, it is determined what types of data Skok mentioned about calques and the process of calqueing, and the place and function of calqued language units in the entry structure is examined. In the conclusion, some methodological guidelines on the presentation of calques in the etymological dictionary are formulated, based on the analysis of Skok’s lexicographic procedure.